Associations Between Prolonged Intubation and Developing Post-extubation Dysphagia and Aspiration Pneumonia in Non-neurologic Critically Ill Patients - Kim, Min Jung (Ann Rehabil Med, 2015)
OBJECTIVE: To identify the associations between the duration of endotracheal intubation and developing post-extubational supraglottic and infraglottic aspiration (PEA) and subsequent aspiration pneumonia. METHODS: This was a retrospective observational study from January 2009 to November 2014 of all adult patients who had non-neurologic critical illness, required endotracheal intubation and were referred for videofluoroscopic swallowing study. Demographic information, intensive care unit (ICU) admission diagnosis, severity of critical illness, duration of endotracheal intubation, length of stay in ICU, presence of PEA and severity of dysphagia were reviewed. RESULTS: Seventy-four patients were enrolled and their PEA frequency was 59%. Patients with PEA had significantly longer endotracheal intubation durations than did those without (median [interquartile range]: 15 [9-21] vs. 10 [6-15] days; p=0.02). In multivariate logistic regression analysis, the endotracheal intubation duration was significantly associated with PEA (odds ratio, 1.09; 95% confidence interval [CI], 1.01-1.18; p=0.04). Spearman correlation analysis of intubation duration and dysphagia severity showed a positive linear association (r=0.282, p=0.02). The areas under the receiver operating characteristic curves (AUCs) of endotracheal intubation duration for developing PEA and aspiration pneumonia were 0.665 (95% CI, 0.542-0.788; p=0.02) and 0.727 (95% CI, 0.614-0.840; p=0.001), respectively. CONCLUSION: In non-neurologic critically ill patients, the duration of endotracheal intubation was independently associated with PEA development. Additionally, the duration was positively correlated with dysphagia severity and may be helpful for identifying patients who require a swallowing evaluation after extubation.